Management Model: A Framework for Evaluation of Alternative Mergers in the Wake of Down-Turn - Maheswara Reddy, D.; Prasad, K. V. N.; Reddy, C. R. (Indian Journal of Finance, 2012)
The paper analyzes the factors hindering the success rate of mergers and acquisitions during the economic downturn scenario. In today’s world economic scenario, from various research studies, it has been found that 50 to 60 percent of cross border mergers and acquisitions have failed. A splendid effort is made to know the reasons for failure of cross border mergers and suggest the possible merger combinations using the integrated techniques of value creation model, value based planning and Herfindahl-Hirschaman Index in this paper. And this research paper concludes with the emergence of Aurobindo-Ranbaxy Limited as the result of merger of Aurobindo Pharma with Ranbaxy Laboratory as a feasible, possible and viable merger instead of the one with Cipla Laboratories Limited.